1999
DOI: 10.1177/155005949903000303
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Evoked Responses to Single Tones and Closely Spaced Tone Pairs in Children Grouped by Reading or Matrices Abilities

Abstract: Long latency auditory evoked responses (AER) were formed to single tones and rapid tone pairs. Using the t-statistic SPM technique, children with poorer WIAT reading scores demonstrated group difference overlying the left parietal and frontal language regions but just for AER to tone pair stimuli. Variables derived from these regions were not significantly different when the same subjects were grouped by K-BIT Matrices scores. When the same children were regrouped by Matrices scores and compared using the SPM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…For example, Tallal and Piercy (1973a, b) demonstrated that normal children were able to discriminate two 75-msec tones separated by an interstimulus interval (ISI) as short as 8 msec, while individuals with SLI required an ISI exceeding 300 msec to perform the same discrimination at the same level of accuracy. Similar rate-specific auditory processing deficits have been observed in dyslexics' behavior and neurophysiology, using both speech and nonspeech stimuli (Duffy, McAnulty, & Waber, 1999;Helenius, Uutela, et al, 1999;Nagarajan et al, 1999;Talcott, Witton, et al, 1999;Ribrary et al, 1998;Witton, Talcott, et al, 1998;Hari & Kiesila, 1996;Kraus et al, 1996;Elliott & Hammer, 1988;Elliott, Hammer, & Scholl, 1989;Reed, 1989;Tallal, 1980). These accumulated findings (see also Leonard, 1998;Farmer & Klein, 1995;Catts, 1993 for reviews) overwhelmingly support the view that individuals with developmental language disabilities have a fundamental dysfunction in the ability to process brief auditory stimuli followed in rapid succession by other acoustic information (i.e., rapid auditory processing).…”
Section: Introductionmentioning
confidence: 72%
“…For example, Tallal and Piercy (1973a, b) demonstrated that normal children were able to discriminate two 75-msec tones separated by an interstimulus interval (ISI) as short as 8 msec, while individuals with SLI required an ISI exceeding 300 msec to perform the same discrimination at the same level of accuracy. Similar rate-specific auditory processing deficits have been observed in dyslexics' behavior and neurophysiology, using both speech and nonspeech stimuli (Duffy, McAnulty, & Waber, 1999;Helenius, Uutela, et al, 1999;Nagarajan et al, 1999;Talcott, Witton, et al, 1999;Ribrary et al, 1998;Witton, Talcott, et al, 1998;Hari & Kiesila, 1996;Kraus et al, 1996;Elliott & Hammer, 1988;Elliott, Hammer, & Scholl, 1989;Reed, 1989;Tallal, 1980). These accumulated findings (see also Leonard, 1998;Farmer & Klein, 1995;Catts, 1993 for reviews) overwhelmingly support the view that individuals with developmental language disabilities have a fundamental dysfunction in the ability to process brief auditory stimuli followed in rapid succession by other acoustic information (i.e., rapid auditory processing).…”
Section: Introductionmentioning
confidence: 72%
“…NCM as an anatomical region is quite large, and some researchers have treated it as one entity, presenting results from seemingly random parts of it (e.g., Duffy et al, 1999; Bolhuis et al, 2000, 2001). Efforts have been made to try and divide it into different anatomical or functional sub-regions, albeit not with a general consensus on how to divide it (Maney and Pinaud, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some insight can be derived from a companion neurophysiological study using quantitative electroencephalography (qEEG; Duffy, McAnulty, & Waber, 1999). The same auditory stimuli (pairs of 40-ms duration complex tones) were used to elicit auditory evoked responses (AER) in good and poor readers from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one might predict that poor readers would exhibit deficits as the difficulty of stimulus resolution increased, whether such resolution were related to frequency interval (DeWeirdt, 1988) or to number of differentiating phonetic features of speech stimuli (Mody, Studdert-Kennedy, & Brady, 1997). Following this line of reasoning, it is noteworthy that, compared with good readers, poor readers show a poorer neurophysiological response to closely spaced tone pairs, but not to single tones, which may simply be less effective stressors (Duffy et al, 1999;Nagarajan et al, 1999). One means to test a causal interpretation is to intervene in the system and predict outcome.…”
Section: Discussionmentioning
confidence: 99%